Astrocyte L-Lactate Signaling in the ACC Regulates Visceral Pain Aversive Memory in Rats - Zafar Iqbal; Shu Liu; Zhuogui Lei; Aruna Surendran Ramkrishnan; Mastura Akter; Ying Li (Cells, 2022)
Pain involves both sensory and affective elements. An aspect of the affective dimension of pain is its sustained unpleasantness, characterized by emotional feelings. Pain results from interactions between memory, attentional, and affective brain circuitry, and it has attracted enormous interest in pain research. However, the brain targets and signaling mechanism involved in pain remain elusive. Using a conditioned place avoidance (CPA) paradigm, we show that colorectal distention (CRD magnitude ≤ 35 mmHg, a subthreshold for pain) paired with a distinct environment can cause significant aversion to a location associated with pain-related insults in rats. We show a substantial increase in the L-lactate concentration in the anterior cingulate cortex (ACC) following CPA training. Local exogenous infusion of lactate into the ACC enhances aversive memory and induces the expression of the memory-related plasticity genes pCREB, CREB, and Erk1/2. The pharmacological experiments revealed that the glycogen phosphorylation inhibitor 1,4-dideoxy-1,4-imino-D-arabinitol (DAB) impairs memory consolidation. Furthermore, short-term Gi pathway activation of ACC astrocytes before CPA training significantly decreases the lactate level and suppresses pain-related aversive learning. The effects were reversed by the local infusion of lactate into the ACC. Our study demonstrates that lactate is released from astrocytes in vivo following visceral pain-related aversive learning and memory retrieval and induces the expression of the plasticity-related immediate early genes CREB, pCREB, and Erk1/2 in the ACC. Chronic visceral pain is an important factor in the pathophysiology of irritable bowel syndrome (IBS). The current study provides evidence that astrocytic activity in the ACC is required for visceral pain-related aversive learning and memory.